Forgiveness Therapy: An Empirical Guide for Resolving Anger and Restoring Hope. 2015
DOI: 10.1037/14526-013
|View full text |Cite
|
Sign up to set email alerts
|

Forgiveness education.

Abstract: thE principLEs undErLyinG ForGivEnEss EducationWe considered eight principles when devising forgiveness education:1. the learning should take place in a nonstressful environment, such as a family setting or a classroom. 2. What is discussed initially does not center personally on the child but instead on story characters. the child sees first that story characters have conflicts. next, the child sees that there are many ways to solve and deal with conflicts and that forgiveness is one of those ways. next, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…For any rigorous research program to be successful, a thorough conceptual analysis must precede it. Most scholars agree that forgiveness is not an act of pardoning, condoning, excusing, forgetting, calming down, or reconciling 8,9. Although there is not consensus on the definition of forgiveness in the literature, views on what forgiveness is continue to vary 9,10…”
Section: Definitions Of Forgivenessmentioning
confidence: 99%
See 2 more Smart Citations
“…For any rigorous research program to be successful, a thorough conceptual analysis must precede it. Most scholars agree that forgiveness is not an act of pardoning, condoning, excusing, forgetting, calming down, or reconciling 8,9. Although there is not consensus on the definition of forgiveness in the literature, views on what forgiveness is continue to vary 9,10…”
Section: Definitions Of Forgivenessmentioning
confidence: 99%
“…Despite the growing empirical studies on forgiveness, empirical findings do not determine the defining characteristics of forgiveness. Based on the Aristotelian perspective of defining moral virtues, Enright and Fitzgibbons8 argue that forgiveness is a moral virtue that focuses on the forgiver and an internal motivation to participate in the act of forgiveness and unconditional love. First, the character of the forgiver focuses on a concern for goodness and human welfare, cognitively aware of their actions, internally motivated to do good, and practices a moral behavior that reflects the goodness of heart.…”
Section: Forgiveness As a Moral Virtuementioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, forgiveness-in the sense of allowing students to err until they succeed, and eliminating the assessment of all students by standardized tests (one size fits all)-is not part of the educational conversation about values. In this article we draw on research that has found empirical evidence for the idea that forgiving mistakes people make generates surprisingly positive results (Worthington, 2006;Enright & Fitzgibbons, 2015).…”
Section: Values Education and Forgivenessmentioning
confidence: 99%